Efektivitas penyuluhan perawatan jenazah dan pendampingan posyandu dalam penguatan peran sosial masyarakat di Kelurahan Jodipan - Septiyawati, Eka Putri (Maliki Interdisciplinary Journal, 2026)
Community service activities through the Student Community Service Program (Kuliah Kerja Mahasiswa/KKM) in Jodipan Village aimed to strengthen the community’s socio-religious and health capacities through funeral care counseling and Posyandu assistance. Funeral care counseling was conducted to improve public understanding of fardhu kifayah obligations in accordance with Islamic law, particularly among Muslim women as strategic actors in socio-religious life. The activities were carried out through interactive lectures, discussions, and practical simulations, which successfully enhanced participants’ knowledge, preparedness, and confidence in handling funeral procedures. Meanwhile, Posyandu assistance was implemented to support maternal and child health services through strengthening the capacity of health cadres, monitoring child growth, providing health education, and increasing community participation. The results indicated improvements in religious understanding, social preparedness, and active community involvement in community-based health programs. In addition to functioning as a basic health service unit, Posyandu also served as a medium for community empowerment and social interaction reinforcement. Overall, the participatory, practical, and needs-based community service approach proved effective in establishing a sustainable foundation for community empowerment in Jodipan Village.